2013
DOI: 10.1038/ajg.2012.429
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Early/Missed Colorectal Cancers After Colonoscopy in Older Patients With or Without Inflammatory Bowel Disease in the United States

Abstract: Older IBD patients had a higher rate of early/missed CRCs after colonoscopy. Our finding supports intensive surveillance colonoscopy for older IBD patients as recommended by guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 37 publications
1
49
1
Order By: Relevance
“…In this case, although the cancer existed within an area of active mucosal inflammation, it was indistinguishable from a sporadic cancer due to the absence of the characteristic features of UC-associated CRC. Compared with older patients with non-inflammatory bowel disease, it has been reported that missed colorectal cancers among older patients with UC are less likely to occur in the right-sided colon 3. This case supports the use of meticulous SI, including for cancers in the right-sided colon, in older patients.…”
Section: Descriptionsupporting
confidence: 64%
“…In this case, although the cancer existed within an area of active mucosal inflammation, it was indistinguishable from a sporadic cancer due to the absence of the characteristic features of UC-associated CRC. Compared with older patients with non-inflammatory bowel disease, it has been reported that missed colorectal cancers among older patients with UC are less likely to occur in the right-sided colon 3. This case supports the use of meticulous SI, including for cancers in the right-sided colon, in older patients.…”
Section: Descriptionsupporting
confidence: 64%
“…Previous studies have focused primarily on cancers occurring within 3 to 5 years after the colonoscopic examination; rapidly progressing adenomas or cancers that were present but not detected at the time of colonoscopy would presumably account for these interval cancers. 15,21,29,30,[33][34][35][36][37][38][39][40][41] The number of cancers detected in this study is similar to or lower than the numbers observed in other studies (which often evaluated cancers over a shorter period). 29,30 Interval cancers accounted for only 8.2% of all colorectal cancers detected in our study cohort, and the absolute risk of an interval cancer was relatively low (9.8 interval cancers per 10,000 person-years of follow-up in quintile 1 of adenoma detection rates and 4.8 interval cancers per 10,000 person-years of follow-up in quintile 5).…”
Section: Discussioncontrasting
confidence: 44%
“…Compared with the general population, inflammatory bowel disease (IBD) patients have a significantly higher risk for the development of colorectal cancer (CRC) and of interval CRC [1,2]. Colorectal dysplasia is considered the precursor to CRC, and thus, colonoscopy is recommended to detect and remove dysplasia to prevent CRC, or to detect CRC at an early, curable stage.…”
Section: Introductionmentioning
confidence: 99%